How Digital Games Impact Student Motivation in Science: Meta Analysis - Istiyono, Edi

(untitled) - Retnawati, Heri (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Learning related to games is always interesting to discuss because games promise to stimulate the imagination, spark curiosity, encourage discussion and debate, and enable experimentation and investigation. Various studies related to learning to load games have been conducted and published, making it necessary to examine the impact of games on students’ motivation to learn science. This study aims to compare the success of science learning that uses games with other learning methods, focusing on motivation as the independent variable. This research uses a meta-analysis approach, based on articles published between 2014 and 2023 in Scopus, ERIC, Taylor and Francis, and Dimensions. A total of 51 studies were identified from various countries worldwide. This analysis uses a contrast group model, with moderator variables including publication indexer, school level, motivation indicator, country, and year of publication. The study also examines effect size (ES), outliers, and publication bias using forest plots, funnel plots, and Egger’s test, all analyzed with R software. The results show that digital games affect student motivation in learning general science, with an ES of g = 0.22 (p < 0.001, 95% CI [0.10; 0.34]). The forest plot revealed heterogeneity in the research data, the funnel plot showed the spread of data, and Eggers’ test returned a p-value of 0.25. Possible reasons for these findings, limitations, and future research directions are also discussed.